THE CONCEPT, ESSENCE, FEATURES OF THE METHODS AND TECHNIQUES USED IN TEACHING FOREIGN LANGUAGES - Nigmatullina Almira Shamsunovna (European Journal of Humanities and Educational Advancements, 2022)
This article covers the concept, essence, features of the methods and techniques used in teaching foreign languages. While several methods of teaching foreign languages were used, the Grammatik-translation method, direct methods were covered in the article